Application of Contextual Teaching and Learning (CTL) Components In Telecommunication Network Design and Optimization Course - Firdaus Firdaus; Fatma Dewi (Universitas Islam Indonesia, 2018)
ABSTRACT: One of the academic problems in the Electrical Engineering Undergraduate Program of Islamic University of Indonesia is the thesis work beyond the target time, so the average period of study became over time. Several solutions have been worked out, but the results have not been significant impact. The biggest problem is the lack of research experience and support skills in research. This research proposes a new solution by inviting students to do integrated learning and research in the Telecommunication Network Design and Optimization course. The selected learning model is Contextual Teaching and Learning based on Problem Based Learning. CTL is a teaching-learning strategy that emphasizes the full process of student involvement in order to discover the material learned and relate it to real life situations that encourage students to apply it in their lives. The results can improve the students achievement of competencies and give direct experience to students to conduct the research. This is evidenced by the increase of the average mark from 63.78 to 78.91 and the availability of student to write the good research reports.Keywords: Contextual, problem based learning, integrated learning and research, study periodReceived: 17 January 2018, Revised: 15 February 2018, Accepted: 24 February 2018